Propuesta de un modelo de optimización para la gestión del talento humano en los trabajadores de la Universidad Nacional de Loja. - Castillo Yaguana, Marianela Silvana (2023)
The purpose of this paper was to propose a human talent management model for optimizing the job performance of workers at the National University of Loja in a sample of 49 participants, who have the job title of service assistant and assistant of services in general. The research design was non-experimental, descriptive-exploratory, with a mixed approach, using inductive and analytical methods. The instruments used were: semi-structured interview, addressed to the Administrative Director of the National University of Loja and to the Administrative Specialists of Academic Management of the Faculty of Education, Art and Communication and of the Faculty of Human Health; and the job description sheet for service assistants. Once the research instruments have been applied, it has been possible to reflect that the managers agree and agree to establish a human talent management model that optimizes the work of the collaborators within the institution. In this way, it is feasible to design and propose a management model to guarantee good performance. Keywords: Organic Code, Citizen Security, Public Order, social benefits,